A major practicum report at Allegro Ice Cream-a division of Glory Foods Corporation, R. Castillo St., Davao City - Abarquez, Rodona May Nacion (2009)
For the purpose of training the BSFT students on the actual operations of a food processing, a 288-hour plant practice is being required in their curriculum. The plant practice was conducted at Allegro ? a division of Glory Foods Corporation (GFC) from April 16 to May 4, 2007. The trainee was exposed to the production activities of the plant like raw materials inventory, production line monitoring, sensory evaluation and research and development (R&D). part of the requirements of the practicum is to furnish a documentary of the said training, hence this manuscript. Description of the company, technical analyses of the practices and processing observed, problems encountered and corresponding recommendations to help improve operation of the plant and to maintain standards in processing are included in this document